Chemistry, metals and agency perspectives - Machado, Igor José de Renó (2023)
How can we interpret the agency of metals, following, for example, the laboratories of chemists? Substances such as molecules, from a recurring point of view in these laboratories, have "behaviors." These behaviors are seen as agencies without apprehension of consciousness or "animation." So, in these scientific research contexts, inanimate substances can have agency because they have behaviors that can even be anthropomorphized. Looking at the relationship between the living and the non-living from the point of view of chemists confuses our ways of seeing processes. From this perspective, metal does not oppose the living but, like the living, has behaviors. Furthermore, from the molecular scale and the reflexive perspective of chemists, the question of an opposition between living and non-living entities may not make as much sense. From this perspective, the behavior of certain metals is an essential part of the production of life, marking the relationship between metal and living beings as very relative to the levels and scale of the analysis. In other words, given a particular scale, there is no difference, and what happens in a living organism is an integral part of certain mental behaviors. Based on ex post facto anthropological research (Machado, 2019), we present some examples from laboratory experience and learning chemistry to discuss the questions above.